2021
DOI: 10.3390/md19020089
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Seaweed Polysaccharides and Their Derived Products with Potential for the Treatment of Alzheimer’s Disease

Abstract: Neurodegenerative diseases are among the most widespread diseases affecting humans, and the number of patients is only rising. Seaweed polysaccharide extracts show significant neuroprotective and reparative activities. Seaweed polysaccharides might provide the next big breakthrough in neurodegenerative disease treatment. This paper reviews the applications of seaweed polysaccharides as potential treatments of neurodegenerative diseases. The particular focus is on fucoidan, ulvan, and their derivatives as poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Several studies highlight the use of algal polysaccharides for the treatment of neurodegenerative diseases as referred by Bauer et al [143]. Park et al [144] demonstrated improved memory and learning in mice treated with fucoidan extracts from Ecklonia cava; thus, the study suggests promising results in future human trials [144].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Several studies highlight the use of algal polysaccharides for the treatment of neurodegenerative diseases as referred by Bauer et al [143]. Park et al [144] demonstrated improved memory and learning in mice treated with fucoidan extracts from Ecklonia cava; thus, the study suggests promising results in future human trials [144].…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…contained seven active compounds that inhibited the seasonal influenza viruses A and B in MDCK (Madin–Darby Canine Kidney)-infected cells [ 143 ]. The sulfated polysaccharide fractions from red algae Kappaphycus alvarezii , Porphyridium , and Hypnea musciformis showed strong protective activity against HIV-1-induced T-lymphoblastic cells [ 144 ]. A ZK antigenic protein served as a vaccine against the Zika virus; it can be produced from Schizochytrium sp.…”
Section: Clinically Important Compoundsmentioning
confidence: 99%
“…Sulfated marine glycans have shown a wide range of medical applications, including antiviral activity [ 108 ]. Since the natural host cell receptor, HS is a sulfated GAG using sulfated marine glycans as an antiviral treatment should inhibit virus binding.…”
Section: Potential Prophylactic and Therapeutic Applications Of Gags In The Treatments Of Viral Zoonotic Diseasesmentioning
confidence: 99%
“…GAGs are sulfated polysaccharide chains, so it stands to reason that other polysaccharides, having similar structures and sulfation content, might also provide similar results. Sulfated polysaccharides such as fucoidan are readily available in seaweed globally and could provide another treatment option [ 108 ]. GAGs and their derivatives (some of which have low or no anticoagulant activity) could represent a class of antiviral drugs against a myriad of viruses.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%